GREEN QUR’ANIC HERMENEUTICS AS A NEW PARADIGM OF ECOLOGICAL EXEGESIS IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Muhammad Radiyal,; Achmad Abubakar,; Sohrah, (Jurnal Diskursus Islam, 2025)
This study explores the intersection between Qur’anic interpretation and the global sustainability agenda through the framework of Green Qur’anic Hermeneutics. By re-examining the revelation within the moral horizon of the Sustainable Development Goals (SDGs), this research seeks to demonstrate that the Qur’an not only provides theological foundations for ecological ethics but also offers a comprehensive spiritual framework for environmental sustainability. Employing a qualitative and interpretive method, the study conducts a thematic analysis (tafsīr mawḍū’ī) on selected verses related to environmental balance (mīzān), corruption on earth (fasād fī al-arḍ), stewardship (khilāfah), and moderation (wasatiyyah). These concepts are contextualized within SDG pillars such as clean water, climate action, sustainable consumption, and life on land. The findings reveal that the Qur’anic ecological discourse anticipates modern sustainability paradigms by emphasizing moral restraint, accountability, and the unity of creation under divine order. Moreover, the integration of hermeneutical reflection and environmental ethics provides a new epistemological orientation for Islamic scholarship: from textual exegesis toward eco-ethical praxis. The study concludes that Green Qur’anic Hermeneutics contributes not only to the development of Islamic eco-theology but also to the global effort in realizing SDG principles through faith-based ecological awareness. This approach strengthens the dialogue between religion and environmental science, positioning the Qur’an as a living guide for sustainable civilization.